Manajemen Angka Kemiskinan Ekstrem Terhadap Penurunan Angka Stunting Di Kabupaten Dompu Nusa Tenggara Barat - Andi Tenri Mantikaisih Laras; Dety Mulyanti (Universitas Muhamadiyah Manado, 2023)
The goal of this study was to examine the government's role in addressing severe poverty and lowering stunting rates in the Dompu Regency of West Nusa Tenggara. Poverty and stunting are two major global challenges that affect all countries, including Indonesia. There are various causative elements, including economic and food factors. Children from low-income families are more likely to suffer from stunting due to their inability to meet nutritional needs, as do moms throughout adolescence and pregnancy. As a result, the POAC Management technique is adopted, which stands for Planning, Organizing, Actuating, and Controlling. The data was acquired using reduction analytic techniques, data display, verification, and qualitative descriptive analysis. The study was carried out in Dompu Regency to ensure its relevance.